2015
DOI: 10.1002/jctb.4750
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the dissolution kinetics of limestone - experimental analysis and modeling

Abstract: BACKGROUND: Stricter SO 2 emission regulations for power plants and maritime transport encourage a better understanding of the phenomena involved in wet flue gas desulfurization (WFGD) where limestone dissolution is regarded as one of the rate determining steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 53 publications
2
32
1
Order By: Relevance
“…The metamorphic limestone tested had a higher degree of crystals and a much less porous surface. In fact, our previous investigations on this kind of sample [30] demonstrated that the sedimentary limestone had around ten times more surface in comparison with the metamorphic one. However, it is also demonstrated that the effective surface actually used during the reactions can be very different because of surface-liquid interactions such as zeta potential [31,32] and surface tension [20,33,34].…”
Section: Limestone Analysismentioning
confidence: 75%
“…The metamorphic limestone tested had a higher degree of crystals and a much less porous surface. In fact, our previous investigations on this kind of sample [30] demonstrated that the sedimentary limestone had around ten times more surface in comparison with the metamorphic one. However, it is also demonstrated that the effective surface actually used during the reactions can be very different because of surface-liquid interactions such as zeta potential [31,32] and surface tension [20,33,34].…”
Section: Limestone Analysismentioning
confidence: 75%
“…This could imply that the limestone could be ground to a larger size fraction than usual and exploit the ultrasound enhancement to reduce the energy consumption of the griding process. The two samples investigated in this study have very large differences in terms of structure, age, and composition [9,40]. This reflects on the degree of crystallinity of the samples and in terms of the solid surface.…”
Section: Effects Of Ultrasound On Specific Surface Area Determinationmentioning
confidence: 94%
“…Both samples are considered to be non-porous since the pore volume values measured by means of nitrogen adsorption were equal or less than 0.002 m 3 /g for both samples [9]. The mineral phases of the samples were assessed by X-ray diffraction (XRD) in previous works [39,40]. The samples were crushed using a jaw crusher; after this, the obtained powder was ground by means of a vibratory disc mill and sieved diverse times to the wanted size range.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations